Retinal inner nuclear layer volume reflects inflammatory disease activity in multiple sclerosis; a longitudinal OCT study. Issue 3 (September 2019) - Balk, Lisanne J; Coric, Danko; Knier, Benjamin; Zimmermann, Hanna G; Behbehani, Raed; Alroughani, Raed; Martinez-Lapiscina, Elena H; Brandt, Alexander U; Sánchez-Dalmau, Bernardo; Vidal-Jordana, Angela; Albrecht, Philipp; Koska, Valeria; et al.
Background: The association of peripapillary retinal nerve fibre layer (pRNFL) and ganglion cell-inner plexiform layer (GCIPL) thickness with neurodegeneration in multiple sclerosis (MS) is well established. The relationship of the adjoining inner nuclear layer (INL) with inflammatory disease activity is less well understood. Objective: The objective of this paper is to investigate the relationship of INL volume changes with inflammatory disease activity in MS. Methods In this longitudinal, multi-centre study, optical coherence tomography (OCT) and clinical data (disability status, relapses and MS optic neuritis (MSON)) were collected in 785 patients with MS (68.3% female) and 92 healthy controls (63.4% female) from 11 MS centres between 2010 and 2017 and pooled retrospectively. Data on pRNFL, GCIPL and INL were obtained at each centre. Results: There was a significant increase in INL volume in eyes with new MSON during the study ( N  = 61/1562, β = 0.01 mm 3, p  < .001). Clinical relapses (other than MSON) were significantly associated with increased INL volume (β = 0.005, p  = .025). INL volume was independent of disease progression (β = 0.002 mm 3, p  = .474). Conclusion: Our data demonstrate that an increase in INL volume is associated with MSON and the occurrence of clinical relapses. Therefore, INL volume changes may be useful as an outcome marker for inflammatory disease activity in MSON and MS treatment trials.